8‐Hydroxyquinoline Metal Complexes as Cathode Interfacial Materials in Inverted Planar Perovskite Solar Cells. Issue 16 (26th July 2021) - Sun, Fulin; Liang, Chunjun; Zhang, Huimin; Ji, Chao; Song, Qi; Gong, Hongkang; Li, Dan; You, Fangtian; He, Zhiqun
Abstract: Ion migration is a crucial factor influencing the stability of perovskite solar cells. Insertion of an interfacial layer between the electron‐transporting layer and the cathode is shown to be an effective way to enhance the performance of devices. However, exploring more effective interfacial materials to block ion migration and thus enhance the device stability is still needed. Herein, a series of 8‐hydroxyquinoline metal complexes are employed as cathode interfacial layers (CILs) in inverted planar perovskite solar cells. The devices with CILs exhibit better performance, stability, and reproducibility than the control device without CILs. The introduction of the CILs forms a better energy match between the [6, 6]‐phenyl‐C61‐butyric acid methyl ester layer and the cathode, reduces the contact resistance, accelerates the charge transfer, and suppresses non‐radiative recombination. Moreover, the CILs protect the device from moisture and block the ion diffusions, which is beneficial for device stability. After optimization, the best power conversion efficiency of 20.6% is obtained by using 8‐hydroxyquinoline aluminum (Alq3 ) as a CIL, and the efficiency remains 85% of its initial value after 800 h continuous illumination. Abstract : A series of 8‐hydroxyquinoline metal complexes are employed as cathode interfacial layer in inverted planar perovskite solar cells. The introduction of the interfacial layer significantly accelerates the charge transfer and blocks the ion diffusion, leading to better device performance and stability.